RANCANG BANGUN SISTEM INFORMASI POIN PELANGGARAN SISWA (Studi Kasus: SMAN 8 Bekasi) - Dina Amalia Febrianti (2021)
The process of recording violations at SMAN 8 Bekasi is fairly impractical because there are no facilities available to find the required data and the accuracy is still uncertain. This research aims to solve the problem of recording violations in SMAN 8 Bekasi by designing a new computerized system to manage the process of recording violation points. Waterfall system development is the method used in this study. The approach used by the waterfall model provides a flow of information system development that is done sequentially and sequentially. The creation of a violation point information system involves several stages, for the initial stage is the design of a system that aims to understand each process that runs. For the second phase, it aims to have SMAN 8 Bekasi monitor the faith of students in complying with school rules. In the third phase, the design of research reports related to the Violation Point Recording Information System began. The result of this study is in the form of Student Violation Point Information System SMAN 8 Bekasi based on website application using PHP and MySQL.